Effect of anaesthetic depth on primary postoperative ileus after laparoscopic colorectal surgery: protocol for and preliminary data from a prospective, randomised, controlled trial. Issue 4 (21st April 2022) - Liu, Weifeng; Huang, Wenkao; Zhao, Bingcheng; Zhuang, Peipei; Li, Cai; Zhang, Xiyang; Chen, Wenting; Wen, Shikun; Xi, Guiyang; Luo, Wenchi; Liu, Kexuan
Abstract : Introduction: Primary postoperative ileus is one of the principal factors affecting in-hospital recovery after colorectal surgery. Research on the relationship between anaesthetic depth and perioperative outcomes has been attracting growing attention. However, the impact of anaesthetic depth on the recovery of gastrointestinal function after surgery is unclear. We aimed to conduct a single-centre, prospective, randomised, controlled trial to explore the effect of anaesthetic depth on primary postoperative ileus after laparoscopic colorectal surgery. Methods and analysis: In this single-centre, prospective, patient-blinded and assessor-blinded, parallel, randomised, controlled trial, a total of 854 American Society of Anesthesiologists physical status I-III patients, aged between 18 and 65 years and scheduled for laparoscopic colorectal surgery lasting ≥2 hours, will be randomly assigned to deep anaesthesia group (Bispectral Index (BIS) 30–40) or light anaesthesia group (BIS 45–55). The primary outcome is primary postoperative ileus during the hospital stay. Secondary outcomes were time to gastrointestinal function recovery, another defined postoperative ileus, 15-item quality of recovery score, length of postoperative stay, postoperative 30-day complications and serum concentrations of intestinal fatty acid-binding protein at 6 hours after surgery. Ethics and dissemination: The protocol was approved by Medical Ethics Committee of Nanfang Hospital, Southern Medical University (Approval number: NFEC-2018–107) prior to recruitment. All participants will provide written informed consent before randomisation. Findings of the trial will be disseminated through peer-reviewed journals and scientific conferences. Trial registration number: ChiCTR1800018725.